Short communication: Vocalization of the Long-eared owl Asio otus (Strigiformes, Strigidae) in the Middle Volga, Russia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Andreychev A, Lapshin A, Kuznetsov V. 2021. Short Communication: Vocalization of the Long-eared owl Asio otus (Strigiformes, Strigidae) in the Middle Volga, Russia. Biodiversitas 22: 5325-5330. Both daily and seasonal year-round vocalizations of the Long-eared owl (Asio otus) (Linnaeus, 1758) were recorded in the Middle Volga River region, Russia with the use of digital dictophones. Voice recorders were installed in the daytime for up to 5 days. The maximum duration of continuous operation of voice recorders was about 140 hours. By the time the previous recording was finished, we would arrive and move the recorder to a different location. The Long-eared owl can be classified as a moderately vocalizing bird, with calls recorded during 3 spring months. Peak activity is associated with pre-incubation and incubation periods. In the spring months, calls of the Long-eared owl were recorded from 16.37 h to 03.43 h. In the spring, the Long-eared owl began to cry before sunset (from 1 hour 30 minutes to 3 hours 15 minutes) and after sunset (from 56 minutes to 3 hours 39 minutes). Vocalization started after sunset for an average of 50 minutes. Vocalization always ended before dawn (to 1 h 21 min). Statistically significant differences in the duration of vespers and morning vocalizations were obtained with the use Mann-Whitney U test (Z = -3.08; p < 0.05).
Keywords: Vocalization, Long-Eared Owl, Asio otus, climatic factors, Middle Volga, Russia